On the performance of vertically aligned graphene array membranes for desalination - Toh, William (2022)
In this paper, we perform molecular dynamics simulations to investigate the performance of multilayer graphene slit membranes. Graphene slit membranes at a critical slit size have been found to be promising desalination membranes. In this contribution, it is shown that multilayer slit membranes have the potential to provide significantly better permeability while retaining outstanding salt rejection. Improved permeability of the membrane is achieved by using slits of widths larger than the critical slit size required to reject salt through size exclusion, and desalination of sea water is performed by increased resistance to salt passage through the multilayering. To facilitate the design process of future multilayer membranes, we analyze the flow resistance of the membrane as a combination of electrical resistors in series and show that this analogy works for membranes where the layers possess the same slit size, as well as membranes with layers of different slit sizes. Comparing with single layer graphene membranes, it was shown that it is possible to obtain 55% improvement in permeability without loss in salt rejection capabilities through multilayering. This opens up possibilities for membrane designers to be free from the restrictions of using a single layer graphene slit membrane with a fixed slit width.